Di-HAMP domains of a cytoplasmic chemoreceptor modulate nucleoid array formation and downstream signaling - P. J. Jazleena; Apurba Das; Annick Guiseppi; Fabian Debard; Jaya Sharma; Mutum Yaikhomba; Tâm Mignot; Emilia M. F. Mauriello; Pananghat Gayathri (mBio)
ABSTRACT In bacterial chemosensing, environmental cues are typically sensed by bacterial transmembrane receptors known as methyl-accepting chemotaxis proteins (MCPs). MCPs form highly organized arrays using the bacterial membrane as a scaffold. These arrays amplify the signals and transduce them into a cellular response. The FrzCD cytoplasmic receptor from Myxococcus xanthus is unique due to its ability to bind DNA and use the nucleoid as a scaffold to form arrays. In this study, we identified two HAMP (histidine kinase, adenylyl cyclase, MCP, and phosphatase) domains located between the DNA binding and signaling domains of FrzCD. In vitro experiments demonstrate that the di-HAMP domain restricts FrzCD to a dimeric form in solution and modulate FrzCD affinity for DNA, whereas the signaling domain stabilizes higher-order oligomeric assemblies upon DNA binding. Through fluorescence microscopy and analyses of M. xanthus social behavior, we demonstrate that the impact of the FrzCD HAMP domains on DNA binding and oligomerization significantly influences the formation of Frz clusters on the nucleoid as well as group motility and development. Our results suggest that the di-HAMP domain might have roles not only in signal transduction but also in the plasticity of chemosensory arrays. These observations illustrate mechanisms of regulation of a DNA-bound cytoplasmic array formed by a diffusible MCP.IMPORTANCEOur study identifies the presence of a di-HAMP domain in a cytoplasmic chemoreceptor, FrzCD, from Myxococcus xanthus, and highlights its role in dynamic receptor oligomerization on a DNA scaffold. By controlling receptor oligomerization and subsequently the array formation on the nucleoid, the di-HAMP domain imparts plasticity to receptor arrays. Such plasticity governs cellular responses to external signals and dictates bacterial social behaviors such as group motility and multicellular structure formation.